Incorporating QM and solvation into docking for applications to GPCR targets. Issue 40 (3rd October 2016) - Kim, Minsup; Cho, Art E.
Abstract : Solvation QM/MM docking for GPCR targets. Abstract : A great number of GPCR crystal structures have been solved in recent years, enabling GPCR-targeted drug discovery using structure-based approaches such as docking. GPCRs generally have wide and open entrances to the binding sites, which render the binding sites readily accessible to solvent. GPCRs are also populated with hydrophilic residues in the extracellular regions. Thus, including solvent and polarization effects can be important for accurate GPCR docking. To test this hypothesis, a new docking protocol which incorporates quantum mechanical/molecular mechanical (QM/MM) calculations along with an implicit solvent model is developed. The new docking method treats the ligands and the protein residues in the binding sites as QM regions and performs QM/MM calculations with implicit solvent. The results of a test on all solved GPCR cocrystals show a significant improvement over the conventional docking method.